(untitled) (Jurnal Pembangunan Sosial, 2009)
Students of higher learning institutions inevitably face many problems during their studies. The problems faced are academic stress, time management, adjustment, teaching method, student-lecturer communication, learning environment and heavy workload. Students’ self-esteem and parenting styles also contributed towards such problems. The aims of this study were to identify the contributing factors based on several demographic components, to examine the relations among the factors and to propose some suggestions to help students deal with the problems. A cross-sectional survey was employed and data were collected using questionnaire. A total of 1923 respondents were chosen to participate in the study through stratified-random sampling. Results indicated that adjustment was the most dominant factor among male and female students. Among the most dominant factors based on ethnicity were adjustment, self-esteem, time management, student-lecturer communication and teaching method. There were relationships between academic stress and other factors such as time management, students’ workload, parenting styles, and self-esteem. In addition, adjustment was found to have relationships with time management, self-esteem, learning environment, parenting styles, teaching method, studentlecturer communication and workload. Results also showed female students having a higher level of academic stress compared to their male counterparts. Malay students also had a higher level of academic stress than other ethnic groups. In term of academic discipline, there were significant differences in four factors which were academic stress, workload, learning environment, and parenting styles.